Analisis Intensitas Pencahayaan Dan Reflektan Di Lingkungan Kerja Terhadap Kelelahan Mata Pada Tenaga Kerja Industri Bulu Mata Palsu Di PT. Sung Shim International Purbalingga. - Feriyandi, Feriyandi; Setiani, Onny; Joko, Tri (Jurnal Kesehatan Lingkungan Indonesia, 2007)
ABSTRACT Background : There are approximately 15,000 workers in several spurious eyelash industries in Purbalingga Regency. Since objects being observed are very fine and the tasks need high accuracy, good lighting is therefore highly required. Poor lighting can lead to visual and mental fatigue, stiffness around the eyes, eye damage and the increasing of work accidents. Sufficient intensity and good management of lighting will result a comfort environment in accordance  to achieve a safe  work environment. Method : This research was conducted as  observational study with a cross sectional approach  for 45 samples of workers. Sampling was carried out by using of systematic random sampling. Data of light intensity and reflectance were collected by measurement of light using Lux Meter and assessment of visual fatigue by using Retention Timer. Other data were collected by interviewing workers with age limitation up to 33 years old. Chi Square Test was used to analyze the data of light intensity and reflectance, work years, age, work period, distance of light to object, distance of eyes to object, relative humidity and temperature, and the correlation with the rise of visual fatigue. Result : Light intensity in the knitting section was between 301.5 – 576.7 lux with reflectance of 43.1%-89.6%. Thirty wokers (66.7%) suffered from mild visual fatigue and fifteen wokers, suffered (33.3%) from moderate visual fatigue. Light intensity had  an influence and significant relationship  to the occurring of visual fatigue among workers in the industry of spurious eyelash of  PT. Sung Shim International  (p < 0,05) with  Odd ratio = 10.246 (95% CI : 1.147 - 91.498).  Probability of light intensity factor to cause visual fatigue measured by a regression logistic model  was  82.9% . It was caused by  poor lighting (light intensities were measured  below 500 lux) while 17.1%  was caused by  other factors. Conclusion : Most of the spurious eyelash industry  (68.9%) show  light intensity 301.5-499.5 lux (below the standard) and  only 31.1%   has  light intensity 503.5-576.7 lux (conform the standard). The measurement of reflectance  shwos  60.0%  are not conformance with the standard (33.2%-63.5%)  and only 40.0%    conform the standard in the range of  33.2%-63.5%. 33.3%). All workers suffered mild until moderate visual fatigue with reaction time  range from 247-407 milli second until  421-539 milli second. It is sugessted that all the spurious eyelash industry have to improve the working environment to  maintain the productivity and safety of working environment. Keywords : light intensity, reflectance, visual fatigue